1930
DOI: 10.1085/jgp.14.1.31
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Bactericidal Action of Ultra Violet Light

Abstract: In this study of the bactericidal action of ultra violet light the first paper (1) described the reaction of an 18 hour culture of Staphylococcus aureus to monochromatic radiations. It was shown that the course of the reaction among large numbers of organisms was approximately the same at each wave length studied but that widely different incident energies were required at different wave lengths to produce these similar effects.The second paper (2) discussed the limits of the bactericidal zone, showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1939
1939
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…The photo-irradiated cell dies when the resulting rate of DNA damage exceeds the rate of repair. 26 ria, such as Propionibacterium acne, 14,17,28 and Pseudomonas aeruginosa, 15 even though the peaks of absorption of pyrimidine bases are known to lie outside the blue spectrum; thus other mechanisms may be involved. For example, photodynamic inactivation of the bacteria through excitation of intracellular porphyrins cannot be ruled out, given a recent report that showed that bacterial eradication diminishes with oxygen depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The photo-irradiated cell dies when the resulting rate of DNA damage exceeds the rate of repair. 26 ria, such as Propionibacterium acne, 14,17,28 and Pseudomonas aeruginosa, 15 even though the peaks of absorption of pyrimidine bases are known to lie outside the blue spectrum; thus other mechanisms may be involved. For example, photodynamic inactivation of the bacteria through excitation of intracellular porphyrins cannot be ruled out, given a recent report that showed that bacterial eradication diminishes with oxygen depletion.…”
Section: Discussionmentioning
confidence: 99%
“…photons that kill Escherichia coli (Gates, 1930) and a variety of evidence strongly suggests that the initial lethal damage occurs predominantly and directly in deoxyribonucleic acid (DNA; see, for example, Wacker, 1963). Furthermore, selective inhibition, by U.V.…”
Section: M Gxnsberg and J Jaqqermentioning
confidence: 99%
“…The first series of action spectra of bacterial cell killing by far-UV were reported in the 1920's by Gates (1928Gates ( , 1929Gates ( and 1930. The maximum killing effectiveness was found to be at about 260 nm, which was soon confirmed by others with the same or different bacterial strains (Wykoff, 1932;Hollaender and Dugger, 1936).…”
mentioning
confidence: 84%